Perception on poverty and inequality concerning social housing - Zamfirescu, Irina Maria (Economy Today: An Interdisciplinary Approach to Contemporary Economic Challenges, 2016)
This paper gives an account on the main feature of social housing within Romania and analyzes how the local authorities react to an emergency housing situation. After being evicted from a social building that has been the subject of retrocession, 25 Roma families spent five months in improvised shacks on the street as a form of protest. Local authorities only react at the pressure of civic society and tried to deal with this situation with over bureaucracy. Within this article I debate on the possibility of having in Romania an endemic discriminatory attitude towards the people who are at risk of being homeless.